Comparison of Effect of Silymarin and Ethanol Extract of Trigonella foenum-graecum on Gentamicin Induced Nephrotoxicity in Rats (Journal of Current and Advance Medical Research, 2019)
Background: A variety of drugs and chemicals possess nephrotoxic potentials; therefore it is of keen interest to the researchers to obtain ways and means for alleviation of nephrotoxicity.Objective: The present study was designed to compare the ameliorative effect of silymarin with ethanol extract of Trigonella foenum-graecum in an experimental model of gentamicin- induced nephrotoxic rats.Methodology: This animal study was conducted by giving distilled water intraperitoneally to control group for seven days (1ml/rat/day) and was sacrificed on 8th day. To induce nephrotoxicity, gentamicin (GM) was administered (80 mg/kg/day for 7 days) intraperitoneally and sacrificed on 15th day. The ethanol extract of T. foenum-graecum was administered (500 mg/kg/day for 14 days) orally concomitantly with GM (7 days) and sacrificed on 15th day. To another group of rats, silymarin was administered (500 mg/kg/day for 14 days) orally concomitantly with gentamicin (7 days) and sacrificed on the 15th day. Biochemical indices like serum creatinine and serum urea levels were estimated to determine nephrotoxicity and amelioration of nephrotoxicity in all rat groups. To determine the status of oxidative stress and lipid peroxidation, the renal cortical glutathione (GSH) and renal cortical malondialdehyde (MDA) levels were estimated.Results: Statistically significant amelioration was observed in all the biochemical parameters in T. foenum-graecum and silymarin treated groups.Conclusion: The ameliorating effect of T. foenum-graecum is much more effective in comparison to that of silymarin in nephrotoxicity.Journal of Current and Advance Medical Research 2019;6(1):23-27